Uji Toksisitas Akut Ekstrak Etanol Daun Salam (Syzygium polyanthum) pada Mencit Jantan (Mus musculus) - Safira Prasita Dewanti; Iswandi Iswandi; Nur Anggreini Dwi Sasangka (Universitas Borneo Lestari, 2023)
The use of bay leaves in traditional medicine basically cannot be separated from the safety aspect. The purpose of this study was to determine the safe limit for using bay leaf extract as well as the qualitative and quantitative indicators of the safe limit for LD50. Thirty animals test were divided into 5 treatment groups, each containing 6 mice at a dose of 0.5% CMC and 800% ethanol extract; 1600; 3200; and 6400. The results obtained with the LD50 based on the decrease in the weight of the test animals at 800 mg decreased to 15.33 grams, 1600 mg decreased to 9.16 grams, 3200 mg decreased to 8.83 grams, and 6400 mg decreased to 8.16 grams. Toxic symptoms in the form of anxiety were the highest in the 800 mg group, the highest decrease in movement activity in the 3200 mg group, the highest weight loss in the 3200 mg and 6400 mg groups, and the highest death in the 6400 mg group. Doses of 800 mg occur in 20% of deaths, doses of 1600 mg and 3200 mg occur in 30% of deaths, and doses of 6400 mg occur in 50% of deaths. The r value obtained is 1,2,2,3 with an f value of 0.50 so that the LD50 value obtained is 2262.03 which is included in the mild toxic category.